INCREASING PEDAGOGICAL COMPETENCE OF ELEMENTARY SCHOOL TEACHERSâ THROUGH LESSON STUDY IN TAMBUSAI DISTRICT ROKAN HULU REGENCY - Erna, Maria; Holiwarni, Betty (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractImprovement of pedagogical competence of Elementary School teachers in Tambusai district, Rokan Hulu regency through the implementation of lesson study (LS) has been performed. Improvement of pedagogical competence of teachers is important to do continously to increase the quality of the learning process. This study is an observational study consisted of two steps, namely socialization and the application treaning of LS. Subjects of the research were elementary school teachers in the Tambusai, Rokan Hulu that consist of 39 teachers. Instrument and data collecting technique of the research is observation and questionnaire. LS socialization method is done by discussion of information. Training of LS has done by applying of three steps: Design lesson {plan), an open lesson (do) and reflection (see). Pedagogical competence that has been analyzed in this study is the assessment of learning implementation plan and the implementation process of learning. The results show that score ratings from learning implementation plan and implementation process of learning made improvement which is from the category K (Less) become C (Enough).Keywords: Do, Lesson Study, Pedagogic Competence, Plan, See